Rolando Costa Ardúz in conversation: About his journey through geography and his participation in the Geographical Society of La Paz - Vargas Condori, Tatiana (2019)
Rolando Costa Ardúz is a renowned intellectual who devoted part of his life to historical-geographical research in Bolivia. He was born in the department of La Paz, in August 1932. Son of Arturo Costa de la Torre, prominent character of the La Paz city , creditor of one of the most important libraries in the country. Dr. Costa Ardúz is a physician, historian, essayist and professor emeritus of the Faculties of Medicine and Law of the Universidad Mayor de San Andrés. He was Vice Chancellor on two occasions and founder of the Geography career at the same university. He has published an infinity of books among which highlight "La Paz, their faces in time" (1993), "Archipiélago de los Paca Haques" (1994), "Monografías de las provincias del departamento de La Paz" (1997), "Historia de la Sociedad Geográfica de La Paz" (2005), among others. Former Vice President of the Sociedad Geográfica de La Paz and the Bolivian Chapter of the Pan-American Institute of Geography and History (IPGH).